Retirement Savings in an Ageing Society: a Challenge for Sustainable Development - Walczak, Damian (Studia Oeconomica Posnaniensia, 2017)
Societies around the world are aging. Regardless of the adopted solutions within the mandatory pension system, the amount of future benefits depends on the ratio of the number of the unemployed to the number of the employed. Therefore, ensuring financial security in old age will increasingly depend on one’s accumulated savings. According to a representative survey Social Diagnosis, Polish people still save little. It needs to be emphasised that the level of this type of savings determines the amount of future pension benefits. Without an adequate organization of the financial market, supported by relevant activities of public sector institutions, there will be no significant change in this regard. This change should have a positive present and future impact on the economic and social aspects of sustainable development. As long as the individual retirement security is deprived of support from the state helping financial institutions in creating incentives for Poles to save, the issue will remain unsolved.